Dry Eye Syndrome in the Practice of a Cataract Surgeon: A Clinical Case - N. V. Maychuk; M. G. Petrova; D. A. Yarkin; N. Sh. Sarhadov (Oftalʹmologiâ)
Relevance. Dry eye syndrome is an important medical and social problem due to its high prevalence and impact on visual functions in human daily life. In cataract surgery, the result of the operation and the patient’s satisfaction directly depends on the preoperative examination, in which, as a rule, the indicators of tear production and the condition of the tear film are most often not taken into account. In this regard, the calculation of the intraocular lens may be incorrect.Purpose. To evaluate the effectiveness of an integrated approach in preparing a patient for cataract surgery with the implantation of a “premium” lens and full recovery in the postoperative period.Materials and methods. A patient applied to YourMed and underwent a standard examination for a refractive patient, including a comprehensive assessment of the condition of the ocular surface. Based on the results of the identified changes, complex therapy was proposed and EDOF IOL with an elongated wavefront was performed. When conducting a study of the condition of the ocular surface using a slit lamp with a module for diagnosing dry eye syndrome (MediWorks, China), signs of an evaporative form of mild (right eye) and moderate (left eye) degree were revealed: the average tear film rupture time was 9.68 (OD) and 2.83 (OS) seconds, the height of the lacrimal meniscus is 0.22 mm (OD) and 0.17 mm (OS), the thickness of the lipid layer is grade 3 (OD) and grade 2 (OS), the percentage of non-functioning meibomian glands is 35 % (OD) and 44 % (OS). In this regard, a comprehensive treatment of SSG has been prescribed (eyelid self-massage, instillation of drops). Two weeks after the therapy start and against its background, the patient again underwent a repeated examination of the condition of the ocular surface, in which positive dynamics was noted. A sequential uncomplicated surgery was performed to replace the lens with an intraocular IOL with an elongated wavefront, first to the left, and after 1 week to the right eye. The patient does not notice any discomfort (dry eyes, watery eyes) that were present before the start of therapy before surgery.Conclusion. Diagnosis of dry eye syndrome, differentiation of the form of this pathology and mandatory complex therapy before lens replacement surgery plays an important role in cataract surgery, which allows you to obtain stable indicators of visual functions in a shorter period after surgery.